THE USE OF PICTURE BOOK IN TEACHING READING FOR JUNIOR HIGH SCHOOL STUDENTS - Maulana Restanto (Journal of English and Education, 2016)
The research was aimed at discovering the use of picture book in helping junior high school students learn reading narrative, and the students’ responses to the use of picture book in teaching reading for junior high school students. The picture book in this research was Dr. Seuss's "The Lorax" book and the students in this research were second grade junior high school students. The qualitative method was delivered in order to collect the data with observation and questionnaire as the instruments of the research. The use of “The Lorax” book as the tool of picture book was believed to be helpful in students’ learning reading activity for junior high school by facilitating teacher and students to carry out all of the steps in reading narrative activities proposed by some experts. The result displayed that picture book has important roles in helping students learn reading narrative with more than 50% responses were positive.